2017
DOI: 10.1002/cmdc.201700636
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Structural Overview of p38α Mitogen‐Activated Protein Kinase in Complex with ATP‐Site and Non‐ATP‐Site Binders

Abstract: Herein we review all the currently available ATP‐site and non‐ATP‐site ligands bound to p38α mitogen‐activated protein kinase (MAPK) available in the RCSB Protein Data Bank (PDB). The co‐crystallized inhibitors have been classified into different families according to their experimental binding mode and chemical structure, and the ligand–protein interactions are discussed using the most representative compounds. This systematic structural analysis could provide some take‐home lessons for drug discovery program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…Consisting of four members (α, β, γ, δ), the p38 MAPK kinases respond to environmental stress and cytokines while displaying differential tissue expression 43,44 . Since its discovery in 1994, p38α has been the best-studied isoform, and while dozens of inhibitors have been developed for clinical trials, none have demonstrated the efficacy and safety needed to receive Food and Drug Administration (FDA) approval 4547 . Alternatively, p38δ is not only an understudied stress-sensing kinase with roles in cancer and diabetes, but its constrained ATP-binding pocket has made discovery of selective inhibitors difficult 4851 .…”
Section: Introductionmentioning
confidence: 99%
“…Consisting of four members (α, β, γ, δ), the p38 MAPK kinases respond to environmental stress and cytokines while displaying differential tissue expression 43,44 . Since its discovery in 1994, p38α has been the best-studied isoform, and while dozens of inhibitors have been developed for clinical trials, none have demonstrated the efficacy and safety needed to receive Food and Drug Administration (FDA) approval 4547 . Alternatively, p38δ is not only an understudied stress-sensing kinase with roles in cancer and diabetes, but its constrained ATP-binding pocket has made discovery of selective inhibitors difficult 4851 .…”
Section: Introductionmentioning
confidence: 99%
“…While potency, selectivity and SAR data is available for several individual p38α inhibitors; Astolfi and colleagues were the first to systematically assess these from a structural perspective [reviewed in Astolfi et al (2018)]. Both ATP-competitive and non-competitive molecules have been identified such as VX-745 (neflamapimod), MW150 and the related MW181, PH-797804, BMS-582949, PF-03715455 and an allosteric binder.…”
Section: Small Molecule Inhibitorsmentioning
confidence: 99%
“…Both ATP-competitive and non-competitive molecules have been identified such as VX-745 (neflamapimod), MW150 and the related MW181, PH-797804, BMS-582949, PF-03715455 and an allosteric binder. Notably, multiple structures have been generated with both ATP-and non-ATP site binders, often through an attempt to improve on selectivity profiles (Fitzgerald et al, 2003;Swahn et al, 2005;Sack et al, 2008;Scior et al, 2011;Arai et al, 2012;Getlik et al, 2012;Astolfi et al, 2019) and reviewed in Astolfi et al (2018).…”
Section: Small Molecule Inhibitorsmentioning
confidence: 99%
“…For the synthesis of 1-(4-nitrophenyl)-3-(trifluoromethyl)-1H-pyrazol-5-amine (61), a one-pot synthesis with ethyl 2,2,2-trifluoroacetate (58) as starting material was used, which was reacted with acetonitrile and potassium tert-butoxide in tetrahydrofuran (Scheme 2). The 4,4, produced in situ was then heated with (4-nitrophenyl)hydrazine hydrochloride (60) in hydrochloric acid and ethanol without further purification to obtain 61 in a yield of 46%. 49) using an Fe-catalyzed Béchamp reduction under mild conditions to obtain compound 62 (Scheme 3).…”
Section: Chemistrymentioning
confidence: 99%
“…By transcriptionally regulating the production of cytokines such as interferon-γ (INF-γ) and tumor necrosis factor-α (TNF-α), p38 MAPK also plays a key role in autoimmune diseases, such as rheumatoid arthritis, psoriasis, diabetes mellitus and multiple sclerosis [1,2]. Because of its strong association with disease development, p38α emerged as a promising drug target [3][4][5]. However, to date, no p38α inhibitor has been approved for treatment.…”
Section: Introductionmentioning
confidence: 99%